STRATEGI GURU MI DALAM MENUMBUHKAN MINDSET TUMBUH (GROWTH MINDSET) SISWA MELALUI PEMBELAJARAN BERBASIS REFLEKSI ISLAMI (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The modern educational paradigm requires students to possess a growth mindset to adapt to learning challenges. However, preliminary observations at MI Ma’arif Sidomukti Kebomas Gresik showed that several students still demonstrated a fixed mindset, such as fear of failure, low self-confidence, and reluctance to try new tasks. This study aims to analyze teachers’ strategies in fostering students’ growth mindset through Islamic reflective learning. The research employed a qualitative case study approach using observation, in-depth interviews, and documentation techniques. The findings revealed four main strategies implemented by teachers: (1) motivational Islamic feedback, (2) habituation of self-reflection (muhasabah), (3) integration of inspiring Islamic figures’ stories, and (4) religious reflective projects. The implementation of these strategies increased students’ courage in facing learning challenges from 29% to 76% within one month. The study concludes that Islamic reflective learning effectively develops students’ growth mindset through spiritual reinforcement, learning motivation, and courage to face failure